EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN PROJECT BASED LEARNING DALAM MENINGKATKAN MINAT BELAJAR SISWA DI SEKOLAH DASAR - Ananda Dewi Anjani; Mahilda Dea Komalasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effectiveness of using the Project Based Learning model in increasing student interest in learning in elementary schools. The lack of interest and participation of students, especially in science learning, makes students less active in learning activities. This study uses a quasi-experimental method. The sample in this study consisted of 43 students, namely 22 students in the experimental class and 21 students in the control class. Data analysis was performed using a t-test with the help of SPSS. The results showed that students taught using the Project Based Learning model scored higher than students taught using the Direct Instruction model, with a significance value of 0.044 < 0.05, proving that there was a significant difference. Thus, it can be concluded that the application of the PjBL model is effective in increasing student interest in learning. Keywords: Project Based Learning, Interest in Learning